Philosophical Background of Computational Thinking - Malčík, Martin; Rakowski, Roman; Miklošíková, Miroslava; Zemčík, Tomáš; Feber, Jaromír (International Journal of Emerging Technologies in Learning (iJET), 2023)
The presented study deals with the philosophical background of computational thinking, which is currently widespread in educational programs across all types of education. The current era is characterized by a turn to the digital environment, which is organized especially by algorithms and the collection of big data. New technologies have literally become the backdrops of our everyday life. The problem, however, is that society uses new technologies as black boxes, which also leads to the fact that it is difficult to adequately interpret and change this technological totality (technological or digital sublime). Computational thinking thus offers a cognitive tool for navigating this technological turn. It also seems that computational thinking can serve as a flexible thinking tool in the context of Society 4.0.